Critical angle threshold using local synchrophasors for real time angular instability detection. Issue 24 (2nd July 2020) - Kumar, Deepa S.; J S, Savier
Abstract : An affordable, stable, reliable and sustainable power supply is the need of the hour, keeping in view the journey to a smart green grid. The present study and derivation of adaptive critical angle threshold (ACAT) contributes to this effect. The ACAT serves as a key index and an indicator to grid operator in proactive mitigation of angular instability in the grid, which is seen to be one of the major initiator of blackouts worldwide. The synchrophasor technology enables accurate calculation of ACAT on real time basis by time synchronised sampling of local voltage and current phasors. The real time calculation makes the index adaptive to variation in system topologies as well as system vulnerabilities. Furthermore, the local system model formed for deriving ACAT has less computational burden while capturing the dynamics of external system, without requirement of intricate power system details. The angular separation of the station bus under supervision can be monitored with respect to the critical angle and serve as a key indicator for initiation of preventive actions during contingencies. The devised methodology is tested using standard IEEE test systems as well as a practical 400/220 kV state grid system using ETAP/MATLAB.